Safety and Security Issues in Technical Infrastructures - Rehak, David 1978; Bernatik, Ales 1972; Dvorak, Zdenek 1961; Hromada, Martin 1983 (Advances in information security, privacy, and ethics (AISPE) Book Series, 2020)
"This book presents a current overview and new trends of the safety and security issues in technical infrastructures"--